(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The journey of transgender people in India is examined in this essay, starting from their veneration in antiquity and ending with their marginalization during the colonial era and eventual rebirth in contemporary legal and social discourse. Examining how religious texts and social duties reflect the deep cultural origins of gender variation in Indian society, it pays particular attention to the hijra community's notable involvement in religious rites and royal courts. Transgender people were systemically marginalized and criminalized because of British colonial control, which imposed draconian laws including the Criminal Tribes Act of 1871. This legacy remained after independence.